First Report of Sclerotinia Rot of Komatsuna, Brassica campestris L., by Sclerotinia sclerotiorum in Japan - SHIMADA, Ryutaro; HOSHI, Hideo; TAKEUCHI, Jun (Annual Report of the Kanto-Tosan Plant Protection Society, 2006)
Sclerotinia rot of komatsuna, a leafy variety of Brassica campestris L., occurred in Tokyo Metropolis in 2003. The causal fungus isolated from the diseased plants was identified as Sclerotinia sclerotiorum (Libert) de Bary. Inoculation tests showed that this fungus was the causal agent of this disease. This is the first report on the disease in Japan.